The cognitive semantics of human and animal anatomy in Andean culture - Cisneros Ayala, Claudia (2020)
In this paper, the role played by the category of singularity of body parts that are pairs or multiple in Andean culture is explained. First, methodologically, the information was collected by interview. Second, the data obtained were systematized according to the functioning of natural logic and thought in the Andean worldview. Third, body parts were analyzed according to parity and multiplicity, including the elements of nature. Finally, the results showed that, when it refers to parts of the body that are pairs or that are considerated to be conformed by more than two entities, the singular number is assigned in the Andean cognitive semantics. In addition, some elements of nature were also marked with singular number, such as flower petals, farm potatoes and a pair of oxen.